Activation of Ca2+-dependent K+ channels contributes to rhythmic firing of action potentials in mouse pancreatic beta cells - Gopel, S; Kanno, T; Barg, S; Eliasson, L; Galvanovskis, J; Renstrom, E; Rorsman, P (1999)
We have applied the perforated patch whole-cell technique to 13 cells within intact pancreatic islets to identify the current underlying the glucose-induced rhythmic firing of action potentials. Trains of depolarizations (to simulate glucose-induced electrical activity) resulted in the gradual (time constant: 2.3 s) development of a small (< 0.8 nS) K+ conductance. The current was dependent on Ca2+ influx but unaffected by apamin and charybdotoxin, two blockers of Ca2+-activated K+ channels, and was insensitive to tolbutamide (a blocker of ATP-regulated K+ channels) but partially (>60%) blocked by high (10-20 mM) concentrations of tetraethylammonium. Upon cessation of electrical stimulation, the current deactivated exponentially with a time constant of 6.5 s. This is similar to the interval between two successive bursts of action potentials. We propose that this Ca2+-activated K+ current plays an important role in the generation of oscillatory electrical activity in the β cell.